Geometric constraints of endothelial cell migration on electrospun fibres - Ahmed, Maqsood (Sci Rep, 2018)
Biomaterial scaffolds that can form a template for tissue growth and repair forms the basis of many tissue engineering paradigms. Cell migration and colonisation is an important, and often overlooked, first step. In this study, fibrous guidance structures were produced via electrospinning and the effect of physical features such as fibre diameter (ranging from 500 nm to 10 μm) on endothelial cell migration was assessed. Using a modified wound healing assay, fibre diameter was found to have a significant effect on the rate of wound closure and the peak migration velocity of the cells with scaffold diameter shown to influence both morphology and alignment of the migrating cells. The expression, phosphorylation and distribution of focal adhesion kinase (FAK) was disrupted on the different scaffolds with small-diameter scaffolds exhibiting increased FAK phosphorylation with the kinase present in the cytosol whereas on large-diameter scaffolds FAK was largely restricted to focal adhesions at the cell periphery. This study demonstrates that electrospun scaffolds can be used to model cell migration on fibrous substrates, and particularly for the studying effects of physical features of the substrate, and that FAK is a key mediator of cell-scaffold interactions on migrating cells.